Factors affecting cattle herd size among smallholder farmers in Timor-Leste - Daci Lelo, Antonio Vicente; Saiyut, Pakapon; Suriya, Patcharee (วารสารแก่นเกษตร, 2023)
Smallholder farmers in Timor-Leste have been involved in raising cattle for a long time, but the cattle herd size per household has not increased significantly. The main objective of this study was to analyze the factors affecting the cattle herd size among smallholder farmers in Timor-Leste. In this study, a multi-stage random sampling technique was employed to select one hundred smallholder cattle farmers in Timor-Leste as respondents, and data were collected through a well-structured questionnaire. Descriptive statistics and an Ordinary Least Square (OLS) multiple regression analysis were employed to analyze the data. The results found that most smallholder cattle farmers in Timor-Leste were male, illiterate, and raised cattle for non-commercial purposes with limited land. The Bali breed was common, and natural mating with their own bull was practiced. The cattle were mainly fed with native grass, rice straws and plant leaves, including leucaena, turi, banana, and waru leaves. The smallholder cattle farmers had an average net farm income of 511.44 USD in 2017 and an average of 16 heads per farm. The OLS regression analysis results found that the number of laborers working in cattle production had a significantly positive effect on the cattle herd size among smallholder farmers in Timor-Leste at P<0.01, while the number of lands for cattle rearing, education, and household total income had a significantly positive effect at P<0.05, but net farm income had a significantly negative effect at P<0.01. To increase cattle herd size among smallholder farmers in Timor-Leste, key policy recommendations include reinforcing the cattle rearing workforce, facilitating land access through redistribution and leasing, providing cattle husbandry education, and promoting the integrated farming, such as combining cattle rearing with crop cultivation or coffee production. These integrated strategies are poised to uplift both cattle production and farmers' livelihoods.